IMPLEMENTASI SISTEM BACKUP DATA PADA SISTEM INFORMASI PERPUSTAKAAN UNIVERSITAS PENDIDIKAN GANESHA - Surya Mahedy, Kadek (Universitas Pendidikan Ganesha, 2021)
In the Ganesha Education University library information system, there is a database stored on the information system server. This database can be accessed online by the academic community of Universitas Pendidikan Ganesha, some technical factors sometimes cause the database system to suffer damage or loss of data, this can be caused by hardware or software, one way to secure the data is to implement several system methods. data backup. This research aims to back up the library information system database and back up the library information system web files. This system developed using the prototyping method with several stages namely: 1. Gathering requirements 2. Building prototyping (model) 3. Evaluation of prototyping 4. Impersonating the system 5. Performing system testing 6. Evaluation of the system 7. System implementation and system usage. The result of this research are a system database in full automatic back up and back up the library information system web files by mirror back up